Lower for longer under endogenous technology growth - Michaela Schmöller; Martin Spitzer (European Central Bank (ECB), 2022)
This paper studies monetary policy strategies under endogenous technology dynamics and low r. Endogenous growth strengthens the gains from make-up strategies relative to inflation targeting, especially if policy space is reduced. This result is due to the long-run non-neutrality of money and the hysteresis effects in TFP through which ELB episodes generate permanent scars on long-run aggregate supply. Make-up strategies not only foster the alignment of inflation with target but also support productivity-improving investment in R&D and technology adoption and hence the long-run trend path, provided that the inherent make-up element is sufficiently pronounced. Inflation is less responsive to monetary policy due to the interaction with productivity dynamics. As a result, additional stimulus is required at the ELB and the degree of subsequent overshooting is alleviated. Endogenous growth also generates novel monetary policy trade-offs, most notably credibility challenges, which can be mitigated by confining make-up elements to ELB episodes.
Keywords: E24; E31; E32; E52; O30; 330; Make-up Strategies; ZLB; Endogenous TFP; Hysteresis; Cycle-Trend Interaction